Strategi Pembelajaran Ilmu Falak di Pesantren(Studi Analisis Strategi Pembelajaran Ilmu Falak Lembaga Falakiyah Annuqayah Kepada Santri di Pondok Pesantren Annuqayah Guluk-Guluk Sumenep) - Mochammad Iqbal Rosyid (JSP: Jurnal Studi Pesantren, 2022)
This research is intended to find out the strategy of learning astronomy of Lajnah Falakiyah Annuqayah at PP. Annuqayah and the impact resulting on santri, pesantren and the surrounding community. The study of astronomy—in various pesantren—began to be less attractive, due to its difficult presumption to learn and master. This can certainly impend the existence of astronomy. Therefore, the idea of updating the methods and strategies of astronomy studying by pesantren is absolutely necessary to ensure the sustainability of this scientific discipline that can instantly have a positive impact on society. There are two questions raised in this paper, that are what are the strategies for learning astronomy at Pondok Pesantrn Annuqayah? and what is its contribution to Pondok Pesantren Annuqayah? The theory used in analyzing this issue is Syaiful Bahri Djamarah's theory of the basic concepts of teaching and learning strategies to achieve goals, including determining the criteria for changes in students' behavior or attitude in accordance with what is desired and expected as a result of learning that has been carried out, choosing effective and targeted learning approaches to achieve learning targets and in accordance with community aspirations, determining and selecting learning techniques, learning methods and learning procedures that are considered the best and most effective that they become the teacher's benchmark when teaching and learning activities take place, and clarifying the measures and criteria for student learning success as a teacher's guide in carrying out evaluations of teaching and learning activities that is undergone. From this, it can be concluded that Lajnah Falakiyah Annuqayah uses an expository learning strategy and its presentation uses a deductive learning strategy which ultimately has a real impact on the lives of students, pesantren and also the surrounding community, especially in the practice of ubudiyah.